Electromagnetic compatibility (EMC). Installation and mitigation guidelines. Installation and mitigation guidelines. Degrees of protection by enclosures against electromagnetic disturbances (EM code) Part 5-7, (15th August 2001) - British Standards Institution,
No abstract available